Exogenous sources of food insecurity in an open developing country - Hermann Dick; Egbert Gerken (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1985)
The vagaries of nature and of world grain markets, causing domestic food production and food import prices to fluctuate, are commonly considered the major external sources of food insecurity in developing countries. The need for steady domestic food production, and for stable world grain prices or international assistance in meeting a fluctuating grain import bill, are accordingly emphasized by the authors. Food self-sufficiency and commodity reserves are also stressed, given barriers to trade. Recent events in Latin American and African countries seem to suggest that erratic capital flows and export earnings, supposedly caused by instabilities of world financial and world primary commodity markets, can be just as detrimental to the maintenance of appropriate food consumption levels. If these claims of additional exogenous sources are subtantiated, the priorities of a food security strategy might need to be reconsidered.
Keywords: 330